An-Gong-Niu-Huang-Wan (AGNHW) regulates cerebral blood flow by improving hypoperfusion, cerebrovascular reactivity and microcirculation disturbances after stroke - Xiao Zhang; Jiamin Pei; Luping Xue; Zhe Zhao; Renhao Xu; Cong Zhang; Cong Zhang; Lijie Fu; Xiangjian Zhang; Lili Cui (Chinese Medicine, 2024)
Abstract Background The restoration of cerebrovascular regulation and improvement of cerebral blood flow in ischaemic regions are crucial for improving the clinical prognosis after stroke. An-Gong-Niu-Huang-Wan (AGNHW) is a famous traditional compound Chinese medicine that has been used for over 220 years to treat acute ischaemic stroke; however, its role in the regulation of cerebral blood flow is still unclear. The aim of the present study was to investigate the regulatory effect of AGNHW on cerebral blood flow and microcirculation after ischaemic stroke and to elucidate the underlying mechanisms involved. Methods Male C57BL/6 mice were subjected to distal middle cerebral artery occlusion (dMCAO) and randomly assigned to the sham, MCAO, or AGNHW groups. AGNHW was administered intragastrically 1 h after dMCAO. The rotarod test was utilized to evaluate behavioural function; TTC was used to determine the infarct volume; and ischaemic injury was assessed by detecting brain levels of SOD, MDA and NO. Then, cortical perfusion and acetazolamide-induced cerebrovascular reactivity were assessed using laser speckle contrast imaging, and the velocity and flux of red blood cells in cortical capillaries were detected using two-photon laser scanning microscopy. In addition, we employed RNA-Seq to identify variations in gene expression profiles and assessed endothelium-dependent changes in microcirculatory dysfunction by measuring vasoactive mediator levels. Results AGNHW significantly increased cerebral blood flow, reduced the infarct volume, and promoted functional recovery after cerebral ischaemia. AGNHW increased the velocity and flux of red blood cells in capillaries and improved cerebrovascular reactivity in the ischaemic cortex. Furthermore, AGNHW regulated endothelium-dependent microcirculation, as evidenced by decreases in the expression of endothelins (Edn1, Edn3 and Ednrb) and the ratios of brain and serum TXB2/6-keto-PGF1α and ET-1/CGRP. Conclusions AGNHW improved cerebral hypoperfusion, regulated cerebrovascular reactivity and attenuated microcirculatory dysfunction within the ischaemic cortex after stroke. This outstanding effect was achieved by modulating the expression of genes related to vascular endothelial cell function and regulating endothelium-dependent vasoactive mediators.